A Simple Method for Quantifying Blastema Growth in Regenerating Planarians. Issue 3 (6th March 2023) - Campillo, Natali; Ireland, Danielle; Patel, Yashvi; Collins, Eva‐Maria S.
Abstract: Due to their strong regenerative capabilities, freshwater planarians are a well‐suited model system for studying the effects of chemicals on stem cell biology and regeneration. After amputation, a planarian will regenerate the missing body parts within 1 to 2 weeks. Because planarians have a distinct head morphology that can be easily identified, head and eye regeneration has been a popular qualitative measure of toxicity. However, qualitative measures can only detect strong defects. Here, we present protocols for quantifying the rate of blastema growth to measure regeneration defects for assessment of chemical toxicity. Following amputation, a regenerative blastema forms at the wound site. Over the course of several days, the blastema grows and subsequently re‐forms the missing anatomical structures. This growth can be measured by imaging the regenerating planarian. As the blastema tissue is unpigmented, it can be easily distinguished from the remaining pigmented body using standard image analysis techniques. Basic Protocol 1 provides a step‐by‐step guide for imaging regenerating planarians over several days of regeneration. Basic Protocol 2 describes the necessary steps for the quantification of blastema size using freeware. It is accompanied by video tutorials to facilitate adaptation. Basic Protocol 3 shows how to calculate the growth rate using linear curve fitting in a spreadsheet. The ease of implementation and low cost make this procedure suitable for an undergraduate laboratory teaching setting, in addition to typical research settings. Although we focus on head regeneration in Dugesia japonica, these protocols are adaptable to other wound sites and planarian species. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Imaging planarians during regeneration Basic Protocol 2 : Quantitative analysis of blastema size with ImageJ Basic Protocol 3 : Quantification of blastema growth rate